Pengaruh Multimedia Interaktif Berbasis Canva Terhadap Pemahaman Konsep IPAS Siswa Kelas V Gugus XIV Kota Bengkulu - Sari, Annisa Rahma; Yusnia (Universitas Bengkulu, 2025)
This study aims to determine the effect of interactive multimedia based on Canva on the understanding of IPAS concepts among fifth-grade students at State Elementary School Fourteen in Bengkulu City. This study uses a quantitative approach with an experimental method using a matching only pre-test–post-test design. The research sample consists of fifth-grade students at State Elementary School Forty-Five in Bengkulu City as the experimental group and fifth-grade students at State Elementary School Forty-Two (SDN Forty-Two) in Bengkulu City as the control group, selected through cluster random sampling. The instrument used was a 5-question essay test administered through pretest and posttest. The data analysis techniques used were descriptive statistical tests, prerequisite tests, and inferential tests. The average posttest score for the control group was 56.67, while the average posttest score for the experimental group was 77.50. The results of the independent sample t-test on the posttest showed that the calculated t-value of 3.539 was greater than the table t-value of 2.023 (df = 41, α = 0.05) and the Sig. (2-tailed) value of 0.001 < 0.05. This indicates a significant difference in the understanding of IPAS concepts between the two groups. The difference in scores is attributed to the different treatments applied to the two groups. Based on this, it can be concluded that interactive multimedia based on Canva has a positive effect on the understanding of IPAS concepts among fifth-grade students at State Elementary School Cluster Fourteen in Bengkulu City